1999
DOI: 10.1021/la980895h
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Regimes in Polyelectrolyte Solutions

Abstract: A general description of the electrolytic conductivity behavior of highly charged strong polyelectrolytes in dilute and semidilute aqueous solutions is presented. For the first time this model considers the influences of the molar mass, charge density (for charge distances less than the Bjerrum length), polyelectrolyte concentration, and the ionic strength adjusted by both the polyelectrolyte concentration (c p in monomol L-1) and added simple salt concentration (c s in mol L-1). Above the overlap concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
78
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 40 publications
10
78
0
Order By: Relevance
“…As it was mentioned above, this discrepancy could be due to the inadequacy of Manning's theory for the quantitative description of the behavior of rather short polyions. As it was shown by Wandrey, [22] in this case the conductivities of the solutions were higher than expected from Manning's theory.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…As it was mentioned above, this discrepancy could be due to the inadequacy of Manning's theory for the quantitative description of the behavior of rather short polyions. As it was shown by Wandrey, [22] in this case the conductivities of the solutions were higher than expected from Manning's theory.…”
Section: Resultssupporting
confidence: 53%
“…At the same time, it was noted that the degree of polymerization of polyions could affect the conductivity of their solutions. [22] In the present work, we studied the influence of the chain length on the conformational behavior of typical flexible water-soluble polyelectrolytes -vinylic polyelectrolytes (PSS) and poly(sodium acrylate) (PA) -in salt-free aqueous solutions. For this purpose, we used different narrow fractions of PSS and PA. For comparison, the same experiments were done with samples of rather rigid native DNA polyanions that differed in the number of base pairs (bp) in the double helix.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been suggested that a description of the electrical double layer by the Debye length is oversimplified in diluted solutions where solution behavior can be conveniently studied by the electrolytic conductivity [11].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, some authors [27][28][29][30] established enhanced counterion condensation by HMW polyelectrolyte. More efficient counterion condensation leads to lower effective charge of macromolecule chain, and as a result, the higher the molecular weight of polyelectrolyte, the more coiled conformation it has [27,31].…”
Section: Electrodeposition Of Panimentioning
confidence: 99%